Mathematical modeling of the melt heating processes in a furnace, producing flat glass (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2000)
The aim of this paper is to present a two-dimensional model of heat-transfer and transport processes in a glass melting furnace and to use this model for investigation of specifical temperature regimes for different heat flows as well as for the different effective thermal conductivity functions. The mathematical model is elaborated on the base of the real flat glass furnace working in Diamond Ltd in Razgrad. The appropriate numerical methods and their performance are discussed as well.